Morphological and hemodynamic changes of sciatic nerves and their vasa nervorum during circular compression and relaxation. (18th September 2020) - Tang, Chun-Wei; Ju, Ming-Shaung; Lin, Chou-Ching K.
Abstract: The main aim of this study was to evaluate the biomechanical and hemodynamic responses of vasa nervorum under transverse circular compression. In situ compress-and-hold experiments were performed on the sciatic nerves of healthy and diabetic rats, and the blood flow within the vasa nervorum was observed using Doppler-optical coherence tomography. A new technique was developed to obtain the time-course of the cross sectional area and the morphology of the vasa nervorum from the tomographic images. A quasi-linear viscoelastic model was used to investigate the overall biomechanical properties of the nerves, and a two-dimensional three-layered finite element model was constructed to analyze the distribution of stress and the morphological changes during the compression-relaxation process. The results showed that the lumenal area of vasa nervorum was reduced in the compression stage, especially for the diabetic nerves. The reduction was greater than 70% when the reduction of the nerve diameter was only 10%. The quasi-linear viscoelastic model showed that normal nerves were more elastic but less viscous than the diabetic nerves. The finite element analyses demonstrated that perineurium could sustain more stress than other layers, while epineurium served as a cushion to protect vasa nervora. In addition, there were regions within epineurium with less stress, so that vasa nervora in these saddle regions were less deformed. The vasa nervorum in diabetic rats was more prone to compression and reduction of blood flow than that of the normal rats. The histological studies supported the simulation results.